Integrated Study of Production Decline Analysis and Streamline Simulation on Haripur Oil Field (Dhaka University Journal of Science, 2019)
In oil and gas industries there are available production data analysis tools and reservoir simulation techniques. Scientists and engineers use these tools and techniques to generate authentic and valuable information on the reservoir for planning and development. In this study production rate decline and streamline reservoir simulation are analyzed integrated way to determine the well life, flow rate, producible reserve, drainage volume and reserve. Well no SY-7 of Haripur oil field produced 0.531 million barrel of oil from 1987 to 1994. Exponential decline rate is matched with production profile and reveals well life of 10 years, producible reserve 0.7 million barrels. In addition, the drainage volume around the well is 158 million cubic feet estimated from the well life by using the streamline simulation, as well as the oil reserve 2 million barrels in the drainage volume is estimated. This reserve information carries value, authenticity and reliability for field development planning.Dhaka Univ. J. Sci. 67(1): 47-50, 2019 (January)